2018
DOI: 10.3389/fpls.2018.00738
|View full text |Cite
|
Sign up to set email alerts
|

The R2R3MYB Gene Family in Phyllostachys edulis: Genome-Wide Analysis and Identification of Stress or Development-Related R2R3MYBs

Abstract: The MYB transcription factor (TF) is one of the largest gene families in plants and involved to multiple biological processes. However, little is known about the MYB family and its functional role in the genome of moso bamboo. In the present study, a total of 114 R2R3MYB genes were first identified from moso bamboo genome and full-length non-chimeric (FLNC) reads. Phylogenetic analysis coupled with gene structure analysis and motif determination resulted in the division of these PheR2R3MYBs into 17 subgroups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 114 publications
3
33
0
Order By: Relevance
“…Moreover, bamboo is known for its fast-growing shoots and widespread rhizomes [2]. It has been reported that several gene families are involved in flower development and abiotic stress [3032, 41], the rapid-growth associated transcription factors remain elusive. The genome sequences of moso bamboo[33] and transcriptome studies [2, 27, 28, 40] provide important platforms for the identification of rapid-growth shoot and rhizome development associated gene families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, bamboo is known for its fast-growing shoots and widespread rhizomes [2]. It has been reported that several gene families are involved in flower development and abiotic stress [3032, 41], the rapid-growth associated transcription factors remain elusive. The genome sequences of moso bamboo[33] and transcriptome studies [2, 27, 28, 40] provide important platforms for the identification of rapid-growth shoot and rhizome development associated gene families.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, large-scale transcriptome analysis has shown that light and phytohormones may play important roles in the rapid-growth of bamboo [2729]. In addition, a large number of transcription factor families are involved in the abiotic stress response and flower development have been studied in moso bamboo [3032]. Although our group has functionally characterized rapid-growth associated key gene- PeGSK1 , the rapid-growth associated transcription factor families are largely unexplored in moso bamboo.…”
Section: Introductionmentioning
confidence: 99%
“…For more accurate identification of Hsf genes in Moso bamboo, multiple database searches were performed according Hou et al [33]. First, Hsf mRNA sequences of Oryza sativa and Brachypodium distachyon, obtained from NCBI Nucleotide database (https://www.ncbi.nlm.nih.gov/) as query sequences to blast against the moso bamboo genome database.…”
Section: Database Searches For Hsf Genes In Moso Bamboo and Analyses mentioning
confidence: 99%
“…To observe the effects of NaCl or mannitol on seed germination and phenotypic differences between WT and OE-PheNAC3 plants, three independent PheNAC3 overexpressing lines (T 3 ) and WT Arabidopsis plants were tested according to method previously methord (Hou et al, 2018). WT and PheNAC3 seeds were sown on 1/2 MS medium solid plates with 150 mM NaCl or 200 mM mannitol, stratified at 4 C for 2 days and then transferred to long-day growth conditions (16 h light/8 h dark cycle at 23 ± 2 C) in a growth chamber.…”
Section: Overexpression and Stress Treatmentsmentioning
confidence: 99%